Extracellular Vesicle-Based Coatings Enhance Bioactivity of Titanium Implants—SurfEV - Taisa Nogueira Pansani; Thanh Huyen Phan; Qingyu Lei; Alexey Kondyurin; Bill Kalionis; Wojciech Chrzanowski (Nanomaterials, 2021)
Extracellular vesicles (EVs) are nanoparticles released by cells that contain a multitude of biomolecules, which act synergistically to signal multiple cell types. EVs are ideal candidates for promoting tissue growth and regeneration. The tissue regenerative potential of EVs raises the tantalizing possibility that immobilizing EVs on implant surfaces could potentially generate highly bioactive and cell-instructive surfaces that would enhance implant integration into the body. Such surfaces could address a critical limitation of current implants, which do not promote bone tissue formation or bond bone. Here, we developed bioactive titanium surface coatings (SurfEV) using two types of EVs: secreted by decidual mesenchymal stem cells (DEVs) and isolated from fermented papaya fluid (PEVs). For each EV type, we determined the size, morphology, and molecular composition. High concentrations of DEVs enhanced cell proliferation, wound closure, and migration distance of osteoblasts. In contrast, the cell proliferation and wound closure decreased with increasing concentration of PEVs. DEVs enhanced Ca/P deposition on the titanium surface, which suggests improvement in bone bonding ability of the implant (i.e., osteointegration). EVs also increased production of Ca and P by osteoblasts and promoted the deposition of mineral phase, which suggests EVs play key roles in cell mineralization. We also found that DEVs stimulated the secretion of secondary EVs observed by the presence of protruding structures on the cell membrane. We concluded that, by functionalizing implant surfaces with specialized EVs, we will be able to enhance implant osteointegration by improving hydroxyapatite formation directly at the surface and potentially circumvent aseptic loosening of implants.